A global regularity result for some degenerate elliptic systems. (September 2015) - Fattorusso, Luisa; Molica Bisci, Giovanni; Tarsia, Antonio
Abstract: We establish a Caccioppoli-type inequality for a second-order degenerate elliptic systems of p -Laplacian type. As a direct consequence, exploiting classical Campanato's approach and the hole-filling technique due to Widman, we are able to prove a global regularity result on Morrey's and L q spaces, with q > p .